2020
DOI: 10.1002/anie.201911078
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Pathogen Infections by Time‐Resolved Chemical Proteomics

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…In a pioneering study, Tao et al reported a photoactivatable multifunctional chemical probe to crosslink bacterial and host proteins during Salmonella internalisation into macrophages. 177 The photoactivatability allowed for time-resolved profiling of pathogen entry and revealed protein–protein interactions at different time points. 177 Indeed, proteins involved in host actin polymerisation, which is important for pathogen internalisation, interacted with microbial proteins during early infection stages, while more nuclear proteins were identified in the late endocytosis process.…”
Section: Discussionmentioning
confidence: 99%
“…In a pioneering study, Tao et al reported a photoactivatable multifunctional chemical probe to crosslink bacterial and host proteins during Salmonella internalisation into macrophages. 177 The photoactivatability allowed for time-resolved profiling of pathogen entry and revealed protein–protein interactions at different time points. 177 Indeed, proteins involved in host actin polymerisation, which is important for pathogen internalisation, interacted with microbial proteins during early infection stages, while more nuclear proteins were identified in the late endocytosis process.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, owing to the fast and controllable cross-linking by photoreactive groups (e.g., diazirine, benzophenone, and phenyl azide), photo-crosslinker provides a general tool to study ligand-directed protein complexes. 128 Zhang et al labeled the living bacteria via a hydrazide moiety on a trifunctional cross-linker that contains diazirine and biotin groups and captured the host cell receptor through UV cross-linking and downstream AP-MS. 129 We developed the Photo-pTyr-scaffold probe by coupling the photoreactive group and the biotin group with an engineering SH2 domain for high-affinity pTyr protein recognition and MS-based profiling of pTyr signaling complexes from clinical tissue samples (Figure 4a). 130 Unlike a trifunctional probe for small molecular ligands with preference to the diazirine group due to its small size, our systematic comparison between diazirine, benzophenone, and the phenyl azide group concluded that the benzophenone group outperformed others for protein ligand application with the combinatory consideration for both labeling efficiency and selectivity.…”
Section: Complex Profilingmentioning
confidence: 99%
“…Alternatively, owing to the fast and controllable cross-linking by photoreactive groups (e.g., diazirine, benzophenone, and phenyl azide), photo-cross-linker provides a general tool to study ligand-directed protein complexes . Zhang et al labeled the living bacteria via a hydrazide moiety on a trifunctional cross-linker that contains diazirine and biotin groups and captured the host cell receptor through UV cross-linking and downstream AP-MS . We developed the Photo-pTyr-scaffold probe by coupling the photoreactive group and the biotin group with an engineering SH2 domain for high-affinity pTyr protein recognition and MS-based profiling of pTyr signaling complexes from clinical tissue samples (Figure a) .…”
Section: Ligand-directed Cross-linking For Protein Complex Profilingmentioning
confidence: 99%
“…Lately, the Tao group developed a chemical probe that permits the capture of host proteins that directly interact with the surface of intracellular Salmonella during infection [ 27 ]. Briefly, the probe features three functionalities: a labeling aminooxy group that conjugates to the glycans on bacterial surface, a photo-reactive diazirine group that crosslinks host-interacting proteins and a biotin group for affinity purification.…”
Section: Large-scale Analyses Of Salmonella Andmentioning
confidence: 99%